The Correlation Between Teachers’ Teaching Style and Students’ Learning Engagement at MA Plus Nurul Islam Sekarbela - Rizkia Rahayu Aji Fahmi; Nawawi Nawawi; Lalu Ali Wardana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Student learning engagement is a multidimensional construct encompassing behavioral, emotional, and cognitive aspects, serving as a cornerstone for academic success. This study investigated the correlation between teachers’ teaching styles and student learning engagement at MA Plus Nurul Islam Sekarbela, addressing a research gap within the unique cultural and institutional environment of Indonesian Islamic schools. Utilizing a quantitative approach with a correlational research design, data were collected from 49 students in grades XI and XII using a structured self-report questionnaire adapted from Grasha’s teaching style model. Descriptive analysis revealed that overall perceived teaching styles were categorized as